MENINGKATKAN KEMAMPUAN MEMASANG PEMBALUT WANITA (SOFTEX) BAGI ANAK TUNAGRAHITA SEDANG MELALUI PENDEKATAN TUTOR SEBAYA - Emilia - (Universitas Negeri Padang, 2012)
Against the background of this research by the issues raised in the Padang Asih SLB Discourse Tunagrahita children were X-class CI / VIII was 19 years old who have difficulty in installing sanitary napkins (softex). It is seen from the capabilities that have not been able to start X in installing sanitary napkins (softex) correctly. The methodology in this research that the single subject research (SSR) with a research design is the AB, the design of a study comparing the ability to install sanitary napkin (softex) in children is X Tunagrahita Baseline conditions and conditions of tretment. Data analysis techniques are used based on the observed data in the form of Analisyis Of Visual Graphics.The results are analyzed include the number of observations in the baseline condition as much as five times and eight times the intervention condition. From the results of this data acquisition can be concluded that the peer tutoring approach can be used to improve the ability to install sanitary napkin (softex) is a class for children Tunagrahita CI / VIII.